PERAN DPRD DALAM PENCEGAHAN KORUPSI KOLUSI DAN NEPOTISME DI DAERAH - Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2015)
As normatively stated in law regulation, in which existence of The Regional Representatives Council (DPRD)has main function to runs legislation function, budgeting function and supervision function. Among those threefunctions, supervision function is actually hold important and strategic in order to create clean and transparentgovernment to bring society welfare. Those function can be played by The Regional Representatives Councilthrough reposition its function in parallel with issues rise in society such as corruption, collution and nepotism.Surely that is not an easy one, since it is needed political commitment to maintain good ethic and good act, the willfrom all of Representative member and Political Party which placed their representative in The Regional RepresentativesCouncil to change and build good image and prove to the public as representative institution thatclean,open, especially related with fund and budget, organized value system through consistency of job andfunction,system running that support internal supervision, faction support to freedom of action of the memberwithoutblocked by political part policy that not pro-people, also reward giving for the representative memberwhodeserve. By looking on those factors, the functions of The Regional Representatives Council especiallysupervisionfunction will effectively take part in prevent corruption, collution and nepotism.